1988
DOI: 10.7164/antibiotics.41.726
|View full text |Cite
|
Sign up to set email alerts
|

A83586C, a new depsipeptide antibiotic.

Abstract: A culture identified as Streptomyces karnatakensis was found to produce a novel cyclic hexadepsipeptide antibiotic designated A83586C.The structure was elucidated by X-ray crystallography, and full XHand 13CNMR assignments are reported. The absolute configuration was confirmed by the detection of D-threonine in the acid hydrolysate of A83586C. A83586Chad potent Gram-positive activity in vitro but lacked in vivo efficacy in mice.During the course of screening for biologically active metabolites, culture A83586,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…The search with these spectroscopic data in AntiBase [9] did not reveal a structure that matched the NMR data, the molecular weight and the empirical formula of 1. However, the search uncovered hexadepsipeptides with similar analytical data: azinothricin [1] (2), A83586C [10] (3), GE3 (4) [2] and citropeptin [11] (5). The similarity of the NMR data with those of 2ϳ5 indicated that the isolated compound might be a related cyclopeptidelactone.…”
Section: Resultsmentioning
confidence: 99%
“…The search with these spectroscopic data in AntiBase [9] did not reveal a structure that matched the NMR data, the molecular weight and the empirical formula of 1. However, the search uncovered hexadepsipeptides with similar analytical data: azinothricin [1] (2), A83586C [10] (3), GE3 (4) [2] and citropeptin [11] (5). The similarity of the NMR data with those of 2ϳ5 indicated that the isolated compound might be a related cyclopeptidelactone.…”
Section: Resultsmentioning
confidence: 99%
“…A culture identified as Streptomyces karnatakensis was found to produce a cyclic hexadepsipeptide antibiotic designated A83586C. A83586C had potent Gram-positive activity in vitro, but lacked in vivo efficacy in mice (Smitka et al, 1988), and also contained FA [155].…”
Section: Epoxy-and Pyrane-containing Fatty Acidsmentioning
confidence: 99%
“…The structure of this antibiotic was elucidated by NMR spectral analysis to be a cyclic hexadepsipeptide closely related to azinothricinl) and A83586C. 2 ) This paper describes the taxonomy of the producing organism and the fermentation, isolation, physicochemical properties and biological activity of citropeptin. …”
mentioning
confidence: 99%